2011
DOI: 10.1080/00933104.2011.10473459
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Controversial Issue Decisions Related to Race, Gender, and Religion During the 2008 Presidential Election

Abstract: Using the 2008 Presidential Election as a case of curricular controversy, the author describes how six high school government teachers responded to the racial, gender, and religious diversity included on the presidential tickets of the two major political parties. Teachers had to decide whether the issue of Americans challenging the tradition of electing White males to the federal executive branch would be deemed "open" or "closed" in their classes, and if they were deemed open, whether they would disclose the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 51 publications
2
42
0
1
Order By: Relevance
“…Although the teachers stated that problems were mostly studentbased, the observation showed that there were also some teacher-based problems. Many international studies (Segall & Gaudelli, 2007;Busey & Mooney, 2014;Camicia, 2008;Hess, 2005;Journell, 2011;Harber & Serf, 2007) found that teacher-based problems were more common than student-based problems in the teaching of controversial issues. According to the results of the observation, a majority of the teachers were not able to manage the teaching of controversial issues and they did not have sufficient skills and experience in this field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the teachers stated that problems were mostly studentbased, the observation showed that there were also some teacher-based problems. Many international studies (Segall & Gaudelli, 2007;Busey & Mooney, 2014;Camicia, 2008;Hess, 2005;Journell, 2011;Harber & Serf, 2007) found that teacher-based problems were more common than student-based problems in the teaching of controversial issues. According to the results of the observation, a majority of the teachers were not able to manage the teaching of controversial issues and they did not have sufficient skills and experience in this field.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Clabough, Philpott, McConkey and Turner (2010) found that one of the reasons that teachers avoided teaching controversial issues is that they did not think they were skilful enough to handle controversial issues. Many studies (Segall & Gaudelli, 2007;Busey & Mooney, 2014;Camicia, 2008;Hess, 2005;Journell, 2011;Harber & Serf, 2007) found that teachers faced problems teaching controversial issues and these issues arose from their academic and occupational inadequacies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12; 2002). Despite strong theoretical support for adding this method in classes (Hess, 2009;Journell, 2011), research continue to show that teachers are hesitant to broach it (Journell, 2013b). Previous studies indicate that the considerable majority of teachers report an emphasis on this method in their teaching hours (Allen, 2003;Crowe & Wilen, 2003;Kelly & Brandes, 2001;Parker & Hess, 2001).…”
Section: Discussing Controversial Issuesmentioning
confidence: 99%
“…in their classrooms (Wilson et al, 2002). Additionally race (Husband, 2012;Washington and Humphries, 2011), environmental issues (Weinberger and Dreyfus, 2013), Darwin (Swanson, 2010), same sex marriage (Diorio, 2011), war on terror (Kuthe, 2011), sexuality issues (Puncher and Klein, 2012), and race, gender and religion (Journell, 2011) are some of the issues found critical by the researchers.…”
Section: Authors Agree That This Article Remain Permanently Open Accementioning
confidence: 99%